Dust in circumstellar disks - Rodmann, Jens (2006)
This thesis presents observational and theoretical studies of the size and spatial distribution of dust particles in circumstellar disks. Using millimetre interferometric observations of optically thick disks around T Tauri stars, I provide conclusive evidence for the presence of millimetre- to centimetre-sized dust aggregates. These findings demonstrate that dust grain growth to pebble-sized dust particles is completed within less than 1 Myr in the outer disks around low-mass pre-main-sequence stars. The modelling of the infrared spectral energy distributions of several solar-type main-sequence stars and their associated circumstellar debris disks reveals the ubiquity of inner gaps devoid of substantial amounts of dust among Vega-type infrared excess sources. It is argued that the absence of circumstellar material in the inner disks is most likely the result of the gravitational influence of a large planet and/or a lack of dust-producing minor bodies in the dust-free region. Finally, I describe a numerical model to simulate the dynamical evolution of dust particles in debris disks, taking into account the gravitational perturbations by planets, photon radiation pressure, and dissipative drag forces due to the Poynting-Robertson effect and stellar wind. The validity of the code it established by several tests and comparison to semi-analytic approximations. The debris disk model is applied to simulate the main structural features of a ring of circumstellar material around the main-sequence star HD 181327. The best agreement between model and observation is achieved for dust grains a few tens of microns in size locked in the 1:1 resonance with a Jupiter-mass planet (or above) on a circular orbit.